Tactile Cartography and visual impairment: a look from the perspective of inclusive education - Medeiros, Ronise Venturini (2019)
This study is configured by a cutout from a term paper, which from the current inclusive school context and the evidence of the importance of teaching resources use for the teaching-learning process of students with visual impairment, aimed to investigate how the Tactile Cartography is used by Geography and Special Education teachers and how it influences the learning process of students with visual disabilities enrolled in public regular education school in the city of Santa Maria - RS. The research is a qualitative approach with a case study method and it was held in a regular public school in the city of Santa Maria - RS. It was found that the Tactile Cartography, more specifically, tactile maps, it is a resource used by Geography and Special Education teachers to blind students, and it contributes positively towards the learning process of Geography concepts. Thus, it is understood that the use of tactile cartographic resources it is essential to the teaching of geographic concepts to students with visual impairment. It is estimated that this study can contribute to the dissemination of the area in Special Education field, and coming to motivate further researches.